Personality competence of Jesus as a teacher based on the gospel of Matthew among Christian religious education teachers - Nugroho, Agus; Daliman, Muner; Purwoko, Paulus Sentot; Uriptiningsih, Ana Lestari (Technium Social Sciences Journal, 2021)
Jesus' personality competence as a teacher based on the Gospel of Matthew is fundamental and important for all Christian Religious Education Teachers. By using descriptive qualitative method, it can be concluded that Jesus' personality competence as a teacher based on the Gospel of Matthew in Christian Education Teachers will have a positive impact. Personal competencies which include: obedience, humility, compassion, firmness, sincerity, and servant character will make the teacher an example for every student served and for those around him, as Jesus is an example for every believer